No Perioperative Pulmonary Complications after Restricted Oxygen Exposition in Bleomycin-Treated Patients: A Short Report. (23rd November 2011) - Wuethrich, Patrick Y.; Burkhard, Fiona C.
Abstract : Hyperoxic exposure during general anaesthesia after receiving bleomycin treatment is purported to potentiate bleomycin-induced pulmonary toxicity. The aim of this study was to retrospectively assess perioperative pulmonary complications after general anaesthesia for retroperitoneal lymphadenectomy in patients who underwent bleomycin treatment <6 months earlier. A consecutive series of 47 patients who underwent surgery after bleomycin treatment were reviewed. Anaesthesia was induced with an inspired fraction of oxygen (FiO2) of 100% for 3 minutes and pertained with a FiO2 just under 30% throughout the procedure. We assessed all potential risk factors for bleomycin-induced pulmonary toxicity. Clinical signs for pulmonary damage were documented preoperatively (dyspnea, tachypnea, nonproductive cough, and postoperative oxygen saturation problems). No pathognomic clinical signs for pulmonary damage were detected up to 7 days postoperatively. Administration of 100% oxygen for 3 minutes during induction of anaesthesia and maintaining a FiO2 < 30% during surgery was safe.